2021
DOI: 10.1037/adb0000690
|View full text |Cite
|
Sign up to set email alerts
|

Racial identity, discrimination, and polysubstance use: Examining culturally relevant correlates of substance use profiles among Black young adults.

Abstract: Objectives: Among Black Americans, young adulthood marks an important developmental period for the initiation of problematic substance use and related health disparities. Unique cultural factors, such as discrimination and racial identity, influence substance use during this period, but it is unknown whether they influence more severe patterns such as polysubstance use. The current study identifies prototypical patterns of substance use among Black young adults and examines whether cultural factors are associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…For example, rates of consuming 5+ drinks and 10+ drinks in a row were greatest among those aged 25–26 years in a national sample of 19–30-year-olds, with rates of both patterns of drinking among those aged 29–30 years being greater than those aged 19–20 years (Schulenberg et al, 2021). Moreover, research to develop and evaluate BAIs for young adults has largely recruited from 4-year predominantly white institutions (PWIs), and these BAIs have frequently been discussed as if they work equivalently across various college subpopulations (Carey et al, 2007) and young adults in general (Tanner-Smith & Lipsey, 2015), despite demonstrable differences across young adult subpopulations in patterns of risk factors for high-risk drinking (e.g., Gilbert et al, 2018; Le & Iwamoto, 2019; Petrova et al, 2019), protective/resiliency factors (e.g., Banks et al, 2020; Straus et al, 2019; Talley et al, 2016), and appropriateness or potential impact of intervention components and modalities (e.g., Gilbert et al, 2018; Lewis et al, 2018; Zemore et al, 2018). These differences call into question how well BAIs developed in samples of college students at 4-year PWIs generalize to other contexts and to specific subpopulations of young adults that may span these contexts.…”
Section: Black Indigenous and People Of Color Young Adultsmentioning
confidence: 99%
“…For example, rates of consuming 5+ drinks and 10+ drinks in a row were greatest among those aged 25–26 years in a national sample of 19–30-year-olds, with rates of both patterns of drinking among those aged 29–30 years being greater than those aged 19–20 years (Schulenberg et al, 2021). Moreover, research to develop and evaluate BAIs for young adults has largely recruited from 4-year predominantly white institutions (PWIs), and these BAIs have frequently been discussed as if they work equivalently across various college subpopulations (Carey et al, 2007) and young adults in general (Tanner-Smith & Lipsey, 2015), despite demonstrable differences across young adult subpopulations in patterns of risk factors for high-risk drinking (e.g., Gilbert et al, 2018; Le & Iwamoto, 2019; Petrova et al, 2019), protective/resiliency factors (e.g., Banks et al, 2020; Straus et al, 2019; Talley et al, 2016), and appropriateness or potential impact of intervention components and modalities (e.g., Gilbert et al, 2018; Lewis et al, 2018; Zemore et al, 2018). These differences call into question how well BAIs developed in samples of college students at 4-year PWIs generalize to other contexts and to specific subpopulations of young adults that may span these contexts.…”
Section: Black Indigenous and People Of Color Young Adultsmentioning
confidence: 99%
“…Although racial identity has been identified as an important factor in substance use behavior of African American adolescents, it has not been examined in relation to different patterns of substance use among this group. One recent study among African American young adults found that positive private regard was inversely associated with cannabis and alcohol co-use, but not alcohol-only use, relative to nonuse (Banks et al, 2021). This points to the importance of considering the impact of racial identity not only in the development of single-substance use, but also in the development of concurrent substance use among African-American youth.…”
Section: Traditional Correlates Of Concurrent Alcohol and Cannabis Usementioning
confidence: 99%
“…Using two or more substances are common patterns of tobacco, alcohol, and cannabis use, [9][10][11][12][13][14] and may be particularly relevant for those experiencing high levels of stress and discrimination 15 such as sexual minority females. 16 Further, some research has shown that patterns of substance use vary based on sexual identity.…”
Section: Introductionmentioning
confidence: 99%